Fiber optic displacement sensor for micro‐thickness measurement - Ahmad, Harith; Yasin, Moh; Thambiratnam, Kavintheran; Harun, Sulaiman Wadi (Emerald, 2012)
Purpose-The purpose of this paper is to propose and demonstrate a simple yet accurate optical fibre based sensor capable of performing micron and sub-micron thickness measurement. Design/methodology/approach-The proposed sensor consists of a multimode plastic probe, three He-Ne lasers and translation stages along with a silicon photodiode and a lock-in amplifier to measure the output voltage as the displacement of the sensor is increased. Findings-The system operating with a source wavelength of 633 nm can provide measurements of up to 3mm with a sensitivity of 0.0054 mV/mm. Originality/value-The thickness of the sample can be obtained from a linear equation correlating the thickness of the sample to the displacement of the sensor at which the peak output voltage is obtained, or by correlating the thickness of the sample directly to the peak output voltage measured.